MSAll strategy for comprehensive quantitative analysis of PEGylated-doxorubicin, PEG and doxorubicin by LC-high resolution q-q-TOF mass spectrometry coupled with all window acquisition of all fragment ion spectra. Issue 22 (12th October 2017) - Yin, Lei; Su, Chong; Ren, Tianming; Meng, Xiangjun; Shi, Meiyun; Paul Fawcett, J.; Zhang, Mengliang; Hu, Wei; Gu, Jingkai
Abstract : Covalent attachment of PEG to therapeutic compounds (PEGylation) is one of the best techniques to improve the biological efficacy of small molecular weight drugs. Abstract : The covalent attachment of polyethylene glycol (PEG) to therapeutic compounds (known as PEGylation) is one of the most promising techniques to improve the biological efficacy of small molecular weight drugs. After administration, PEGylated prodrugs can be metabolized into pharmacologically active compounds so that PEGylated drug, free drug and released PEG are present simultaneously in the body. Understanding the pharmacokinetic behavior of these three compounds is needed to guide the development of pegylated theranostic agents. However, PEGs are polydisperse molecules with a wide range of molecular weights, so that the simultaneous quantitation of PEGs and PEGylated molecules in biological matrices is very challenging. This article reports the application of a data-independent acquisition method (MS All ) based on liquid chromatography electrospray ionization quadrupole time-of-flight mass spectrometry (LC-q-q-TOF-MS) in the positive ion mode to the simultaneous determination of methoxyPEG2000-doxorubicin (mPEG2K-Dox) and its breakdown products in rat blood. Using the MS All technique, precursor ions of all molecules are generated in q1, fragmented to product ions in q2 (collision cell), and subjected to TOF separation before precursor and product ions are recorded using low and high collision energies (CE) respectively in different experiments for a single sample injection. In this study, dissociation in q2 generated a series of high resolution PEG-related product ions at m / z 89.0611, 133.0869, 177.1102, 221.1366, 265.1622, 309.1878, and 353.2108 corresponding to fragments containing various numbers of ethylene oxide subunits, Dox-related product ions at m / z 321.0838 and 361.0785, and an mPEG2K-Dox specific product ion at m / z 365.0735. Detection of mPEGs and mPEG2K-Dox was based on high resolution extracted ions of mPEG and the specific compound. The method was successfully applied to a pharmacokinetic study of doxorubicin, mPEG2K (methylated polyethylene glycol 2K), and mPEG2K-doxorubicin in rats after a single intravenous injection of mPEG2K-doxorubicin. To the best of our knowledge, this is the first assay that simultaneously determines mPEG, Dox, and mPEG2K-Dox in a biological matrix. We believe the MS All technique as applied in this study can be potentially extended to the determination of other PEGylated small molecules or polymeric compounds.